2022
DOI: 10.3390/math10010142
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis and Comparison of Multi-Factor Asset Pricing Model Performance during Pandemic Situations in Developed and Emerging Markets

Abstract: This study empirically analyzes and compares return data from developed and emerging market data based on the Fama French five-factor model and compares it to previous results from the Fama French three-factor model by Kostin, Runge and Adams (2021). It researches whether the addition of the profitability and investment pattern factors show superior results in the assessment of emerging markets during the COVID-19 pandemic compared to developed markets. We use panel data covering eight indices of developed and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…It is interesting to compare these results with those of Kostin et al (2022) on multifactor asset pricing and factor models during pandemic situations in developed and emerging markets. Timor-Leste is one of the new/emerging markets that invest their assets in the form of stocks and bonds in the markets of developed countries such as the United States (US), the United Kingdom (UK), Japan, and Germany.…”
Section: Results Discussionmentioning
confidence: 99%
“…It is interesting to compare these results with those of Kostin et al (2022) on multifactor asset pricing and factor models during pandemic situations in developed and emerging markets. Timor-Leste is one of the new/emerging markets that invest their assets in the form of stocks and bonds in the markets of developed countries such as the United States (US), the United Kingdom (UK), Japan, and Germany.…”
Section: Results Discussionmentioning
confidence: 99%
“…Leite et al (2018) reaffirmed the presence of the value premium in 12 emerging markets from 2007 to 2017 with significant and positive returns of the value minus growth portfolios. Kostin et al (2022) reported monthly value premiums in China and Brazil during the 2000-2020 period at 0.27% and 0.24%, respectively. The Moroccan Stock Exchange's value minus growth portfolio yielded a significantly positive return of approximately 0.8% per month (Taib and Benfeddoul, 2023).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hanauer and Linhart (2015) and Leite et al (2018) looked at emerging markets and ascertained the value premium in the Latin American, Eastern European, and Asia-Pacific markets. The value premium haas also been uncovered in China and Brazil (Kostin et al, 2022), andMorocco (Taib andBenfeddoul, 2023).…”
Section: Introductionmentioning
confidence: 97%
“…During the first quarter of 2020, the COVID‐19 virus, first detected in Wuhan, China, spread rapidly worldwide. In light of this global pandemic, supply chains were disrupted, countries‐imposed lockdowns of varying severity, and prevailing uncertainty tremendously impacted the economy (Kostin et al., 2022; Wiedra et al., 2022). Following Neisen and Schulte‐Mattler (2021), the extent to which the pandemic influenced the economy is still not completely clear, as both the real economy and the financial world were affected.…”
Section: Literature Reviewmentioning
confidence: 99%